Skrining Anemia Pada Remaja Putri Sebagai Upaya Pencegahan Stunting - Sari, Evi Puspita; Arifin, Zainul; Farhan, Anthofani (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Anemia is a non-communicable disease that often occurs in adolescent girls. Anemia in adolescents that is not resolved has the potential to continue into productive age. As a result, pregnant women with anemia will give birth to an unhealthy generation with low body weight, low immunity and stunting. Early detection of anemia needs to be done to prevent various impacts from occurring. The aim of this community service activity is to early detect anemia in young women through checking hemoglobin levels. The method for checking Hemoglobin (Hb) levels uses the Point of Care Testing (POCT) method. The target of this activity is 171 young women. The results of Hb examinations in young women showed that 23.02% had Hb levels less than normal (anemia) and 76.98% had normal Hb levels. It can be concluded that the incidence of anemia in adolescents is still high because it exceeds the 20% threshold.